Pulmonary hypertension in idiopathic pulmonary fibrosis: a review - Corte, T.J.; Wort, S.J.; Wells, A.U. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Pulmonary hypertension (PH) is a common in patients with idiopathic pulmonary fibrosis (IPF) referred for transplantation.When present, PH is associated with increased mortality, and may explain the deterioration of some patients with preserved pulmonary function. PH in IPF may develop as a consequence of, or disproportionate to the underlying fibrotic lung disease. The distinction between these two ‘stages’ of PH is essential as there are key differences in their pathophysiology, identification, and potential treatment options. Treatment advances in idiopathic pulmonary artery hypertension have focused attention on PH associated with underlying lung disease. We focus on pathogenetic mechanisms, identification of PH, and the potential for therapeutic intervention for PH in IPF. Although vascular ablation, and chronic hypoxia are both important in the aetiology of secondary PH, these mechanisms do not explain the development of disproportionate PH. In these patients, the early development of PH may be associated with increased fibrotic cell mediators, abnormal vasculature or response to hypoxia, seen in IPF. Nocturnal and exercise desaturation are common in IPF, and may precede and contribute to the development PH. Therapeutic options for PH in IPF are limited, and there have been no controlled trials. Successful therapeutic intervention in pulmonary arterial hypertension, has led to suggestions that therapeutic intervention with PH specific therapy may be useful. However, controlled trials are warranted before therapy can be recommended. In the design of such trials, the distinction between secondary and disproportionate PH is essential.